2017
DOI: 10.1089/gtmb.2017.0133
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aTNF-αPolymorphism on the Severity of Schistosomiasis Periportal Fibrosis in the Northeast of Brazil

Abstract: Our results suggest the (-308) AA genotype may be a risk factor for severity in advanced PPF, in this Brazilian population, and could potentially be used to predict the severity of advanced PPF in schistosomiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Polymorphisms in the connective tissue growth factor (CTGF) as well as the IL-22 pathway were also observed. In addition, several associations have been reported between severe hepatic fibrosis during Schistosomiasis and genes encoding for IL-13, TNF-α, MAPKAP1, ST2, IL-10, M1CA, HLADRB1, IL-4, ECP, and IFN-γ, have been reported from various studies (Hirayama et al, 1998;Chevillard et al, 2003;Eriksson et al, 2007;Gong et al, 2012;Silva et al, 2014;Zhu et al, 2014;Long et al, 2015;Oliveira et al, 2015;Long et al, 2017;Silva et al, 2017). These observations suggest that while infectious agents such as schistosoma can drive hepatic fibrosis by mediating tissue damage, genetic predispositions to TGF-β pathway activation or a specific inflammatory response may make the hepatic environment conducive to fibrosis in the presence of an infectious agent.…”
Section: Parasitic Infectionsmentioning
confidence: 98%
“…Polymorphisms in the connective tissue growth factor (CTGF) as well as the IL-22 pathway were also observed. In addition, several associations have been reported between severe hepatic fibrosis during Schistosomiasis and genes encoding for IL-13, TNF-α, MAPKAP1, ST2, IL-10, M1CA, HLADRB1, IL-4, ECP, and IFN-γ, have been reported from various studies (Hirayama et al, 1998;Chevillard et al, 2003;Eriksson et al, 2007;Gong et al, 2012;Silva et al, 2014;Zhu et al, 2014;Long et al, 2015;Oliveira et al, 2015;Long et al, 2017;Silva et al, 2017). These observations suggest that while infectious agents such as schistosoma can drive hepatic fibrosis by mediating tissue damage, genetic predispositions to TGF-β pathway activation or a specific inflammatory response may make the hepatic environment conducive to fibrosis in the presence of an infectious agent.…”
Section: Parasitic Infectionsmentioning
confidence: 98%
“…That said, studies in murine models have shown TNF to be an important mediator of granuloma formation and hepatic fibrosis ( 252 ), however, clear distinction between granuloma formation and PPF has to be drawn as we do not know how the two relate. Host genetic studies are contradictory regarding SNPs within the TNF loci; with no observable association between HLA-TNF polymorphisms and presentation with PPF in two Sudanese populations ( 253 ), but an association between a TNF gene SNP and PPF being reported for a Brazilian population ( 254 ). High TNF-alpha levels in response to SEA stimulation have also been shown to be associated with ultrasound detectable bladder morbidity due to S. haematobium infection in Kenyan case-control ( 255 ) and cross-sectional studies ( 256 ).…”
Section: The Role Of the Host In Morbidity Hotspotsmentioning
confidence: 99%
“…Gene polymorphisms may influence TNF-α secretion and disease susceptibility. In addition, TNF-α has been proved to be related to various diseases, such as schistosomiasis, periportal fibrosis (16) and diabetic nephropathy (17). IL-10 is also a cytokine exerting pro-inflammatory effects, and it originates from numerous cells, with a complex mechanism of action.…”
Section: Discussionmentioning
confidence: 99%